Experience in the Use of Artificial Fibrillation in the Correction of Postinfarction Left Ventricular Aneurysms as the Most Appropriate Alternative to Pharmaco-Cold Protection of the Heart - Rudenko, M. L.; Ioffe, N. O.; Vayda, V. V.; Pavlykova-Chertovska, A. A. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Coronary heart disease (CHD) is the leading cause of death in the world. In most cases, the disease is complicated by myocardial infarction (MI) followed by the formation of a left ventricular aneurysm (LVA), ruptures of the interventricular septum, ischemic cardiomyopathy, mitral regurgitation and arrhythmias. Postinfarction left ventricu-lar aneurysm is the most common and severe complication of CHD. There are a lot of methods of LVA surgical correc-tion, including Cooley’s linear repair technique, purse-string technique of Jatene and endoventriculoplasty using the Dor technique. Over the last year, 43 left ventricular aneurysm repair surgeries were carried out at the NatioМешковаnal M. M. Amosov Institute of Cardiovascular Surgery. Depending on the comorbidities, age, left ventricular contractility and other factors, plastic correction was performed using artificial fibrillation (n = 24 [55.8%]) or cardioplegic solution (n = 19 [44.2%]) for myocardial protection. Significant difference in the mean duration of the operation, the time the patient was on the artificial circulation, the amount of inotropic support, the time of mechanical ventilation, and the contractile function of the left ventricle (LV) was observed. In group 1, where artificial left ventricular fibrillation was used for myocardial protection, the mean duration of the surgery was 1.9 ± 0.2 h shorter. Accordingly, the patient’s stay on the artificial circulation decreased by 92.2 ± 0.3 minutes. Also, the duration of mechanical ventilation was significantly shorter: 4.6 ± 0.8 hours and 7.3 ± 0.7 hours in groups 1 and 2, respectively. And most importantly, in the group 1 the ejection fraction increased by 2.3 ± 0.45% compared with 1.17 ± 0.43% in the group 2. However, all the other parameters were similar in both groups. This gives reason to consider artificial ven-tricular fibrillation as the most appropriate method of myocardial protection in the future.